Knowledge, attitudes and practices of mothers/caregivers regarding oral rehydration therapy at Johan Heyns Community Health Center, Sedibeng District - Onwukwe, Sergius Chuks (My University, 2014)
BACKGROUND: Diarrhea is an important health problem and has remained a threat to the lives of children under 5 years old especially in developing regions of the world. Presently, it is estimated that about 1.5 million of these children die every year from diarrhea that would have been prevented by giving oral rehydration therapy (ORT). The value of ORT in treating diarrhea has remained unquestionable but emerging evidence still points to unsatisfactory uptake. This study assessed the knowledge, attitudes and practices of mothers/caregivers regarding oral rehydration therapy at Johan Heyns community health center, Vanderbijlpark. OBJECTIVE: To assess the knowledge, attitudes and practices of mothers/caregivers regarding oral rehydration therapy at Johan Heyns community health center. METHODS: This study was a descriptive cross sectional study involving mothers/caregivers’ attended to by the primary health care (PHC) nurses at the Integrated management of childhood illnesses (IMCI) clinic of a large community health center in Sedibeng district. Respondents were systematically recruited until a sample size of 377 was reached. A face to face questionnaire was used to collect data on demography, knowledge, attitudes, practices and response to diarrhea from the participants. The data collected was analyzed by the use of descriptive statistics, chi-square test and Fisher’s exact test. The main outcome measures were the level of ORT knowledge of mothers/caregivers, attitudes, practices and response to diarrhea. RESULTS: Most of the caregivers were mothers (88.3%) who had completed matric (72.5%) and were unemployed (60.6%). The mean age was 30 years. About 53.3% of the caregivers gave ORT as an initial response to diarrhea, 30.2% took their child to the clinic/hospital, while 4% gave orthodox or traditional medicine. The majority of the caregivers (89.4%) had heard of ORT. The main source of ORT information was clinic/hospital (89.6%). Most of the caregivers (81.7%) said ORT stops diarrhea while 18.3% said it stops dehydration. Many of the caregivers (66%) had used ORT. The caregivers’ORT knowledge was significantly associated with attitude and (P= 0.0000). A small proportion of the caregivers (29%) had problems preparing ORT at home. Most of the caregivers’ children (75.5%) did not like the taste of ORT. The ORT attitude of caregivers was significantly associated with knowledge and practice (P=0.0000; P=0.0127). Less than half (33.7%, n=127) of the entire study sample (n=377) and about half (50%, n=127) of the caregivers who claimed that they could prepare ORT (67.4%, n=254) was able to prepare a correct recipe. Over half (54.2%) of the caregivers stopped giving ORT or did not know what to do when vomiting starts. A large number of the caregivers (72.7%) continued feeding their child at the onset of diarrhea. Many of the caregivers (82.8%) used only ORT at the onset of diarrhea while few (17.2%) added some unconventional remedies. There was no association between ORT practice and ORT knowledge (P=0.4797). CONCLUSION: This study shows a significant association between ORT knowledge and attitude, and also between ORT attitude and practice. There was no correlation between ORT knowledge and practice, therefore ORT knowledge did not satisfactorily translate to the practice. Majority of the caregivers could not prepare ORT correctly and either stopped giving ORT or did not know what to do when vomiting starts. The reported use of unconventional remedies like raw egg and custard by some caregivers to treat diarrhea at home is disturbing. It is obvious that much work still needs to be done to improve home treatment of diarrhea using ORT; a good starting point is to initiate new strategies aimed at improving caregivers’ education on the different aspects of ORT.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the award of a degree of Master of Medicine in Family Medicine
Keywords: Fluid Therapy--in infancy & childhood